The effect of wide resection margin in patients with intrahepatic cholangiocarcinoma: A single-center experience. Issue 28 (July 2016) - Ma, Ka Wing; Cheung, Tan To; She, Wong Hoi; Chok, Kenneth S.H.; Chan, Albert Chi Yan; Ng, Irene Oi Lin; Chan, See Ching; Lo, Chung Mau
Abstract: Introduction: Prognosis of intrahepatic cholangiocarcinoma (ICC) remained poor despite the multitude advancement of medical care. Resection margin status is one of the few modifiable factors that a surgeon could possibly manipulate to alter the disease outcome. However, the significance of margin status and margin width is still controversial. This study serves to further elucidate the role of them. Method: This is a retrospective cohort from the Queen Mary Hospital, The University of Hong Kong. Consecutive patients diagnosed to have ICC and with surgical resection performed in curative intent were retrieved, while patients with cholangiohepatocellular carcinoma, Klaskin tumor, tumor of extrahepatic bile duct, and uncertain tumor pathology were excluded. Results: From 1991 to 2013, there were 107 patients underwent hepatectomy for ICC. Gender predilection was not observed with 58 males and 49 females, median age of the patients was 61. The median tumor size was 6 cm and most of them (43%) were moderately differentiated adenocarcinoma. Clear resection margin were achieved in 95 patients (88.8%) and the median margin width was 0.5 cm. The hospital length of stay and operative mortality were 11 days and 3%, respectively. The disease-free survival and overall survival were 17.5 and 25.1 months, respectively. Multivariate analysis showed that margin width was an independent factor associated with disease-free survival ( P = 0.015, 95% confidence interval [CI] 0.4–0.9). Subgroup analysis in patients with solitary tumor showed that margin width is an independent factor affecting overall survival ( P = 0.048; odds ratio: 0.577; 95% CI: 0.334–0.996). Discriminant analysis showed that the overall survival increased from 36 to 185 months when margin width was >0.9 cm ( P = 0.025) in patients with solitary tumor. Conclusion: Aggressive resection to achieve resection margin of at least 1 cm maximizes chance of cure in patients with early ICC.